Localism and the Design of Political Systems - Harmes, Rick (Taylor & Francis, 2021)
"This book examines localism as a political idea and policy approach and explains what localism is about, why it's growing in importance, and how it relates to other themes in politics. Illustrated with case studies from the UK, mainland Europe and the Indian sub-continent, the book analyses localism in conceptual and theoretical terms and locates it within the overall landscape of political thought. Key themes covered in the book include place, space and scale; decentralization and devolution; multi-level governance; public value; democracy and empowerment; and political design. With the focus on the bottom-up, constructivist aspects of localism, the book argues that localism is most likely to work successfully in a political order where sovereignty is 'distributed' across various social spheres and levels of government. The book offers a comprehensive view of localism by synthesizing its various strands and creating a distinctive framework for design and evaluation. This book will be of particular interest to scholars, students and practitioners of localism, particularly within local and regional government, public administration and policy, human and political geography, and urban studies."